Efektifitas Berbagai Metode Pembelajaran untuk Partisipasi Aktif Mahasiswa dan Stimulasi Proses Clinical Reasoning - Widyandana Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Skills lab program can be conducted by several methods, such as training by mannequin, role play with peers, simulated patients, and training in community. Medical students are expected to play an active role in training and always practice their clinical reasoning skills. However, there are still many students not ready for implementing some medical procedure in their clerkship. Therefore, this study aimed to compare the level of active participation and the clinical reasoning process of students obtained in four learning methods in skills lab.Method: This study used a cross-sectional design with random survey questioner to 150 medical students in Medical Faculty of GMU (n=150). This survey were expected to explore the impression of students to each learning method, particularly in the active participation in practice and the clinical reasoning process. The results were analyzed using descriptive quantitative method by comparing total score of each learning method.Results: The results showed that the learning method of medical skills in community is superior to 3 other methods, namely practice with mannequins, role play with peers, as well as simulated patients, both in promoting the active participation of students and stimulating the clinical reasoning skills (p<0.05).Conclusion: Medical skills training in community is more effective in promoting the active participation of students in practice and stimulating the clinical reasoning skills. However, it should considerate with compatibility of topic, students’ readiness, and combined methods if needed.